2013
DOI: 10.1182/blood-2013-02-485441
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin and pan-class I/II deacetylase (DAC) inhibition is synergistic in preclinical models and clinical studies of lymphoma

Abstract: Key Points Treatment of DLBCL with the combination of sirtuin and DAC inhibitors leads to synergistic cytotoxicity and acetylation of Bcl6 and p53. The overall response rate of relapsed lymphoma patients treated with vorinostat and niacinamide was 24%, and an additional 57% achieved stable disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 46 publications
1
54
0
1
Order By: Relevance
“…One such inhibitor-called 79-6 complex-works by binding to the BCL6 BTB domain corepressor binding groove (41). Strategies such as histone deacetylation inhibition-to overcome the repressive effects of BCL6 on p53 and cell-cycle-inhibitory proteins-are also potentially interesting in DLBCL (43,44). One recent study demonstrated that treatment of DLBCL cell lines with pandeacetylone inhibitors in combination with niacinamide produced synergistic toxicity in GCB over ABC subtypes and led to acetylation of BCL6 and p53 (44).…”
Section: Pre-rituximabmentioning
confidence: 99%
See 1 more Smart Citation
“…One such inhibitor-called 79-6 complex-works by binding to the BCL6 BTB domain corepressor binding groove (41). Strategies such as histone deacetylation inhibition-to overcome the repressive effects of BCL6 on p53 and cell-cycle-inhibitory proteins-are also potentially interesting in DLBCL (43,44). One recent study demonstrated that treatment of DLBCL cell lines with pandeacetylone inhibitors in combination with niacinamide produced synergistic toxicity in GCB over ABC subtypes and led to acetylation of BCL6 and p53 (44).…”
Section: Pre-rituximabmentioning
confidence: 99%
“…Strategies such as histone deacetylation inhibition-to overcome the repressive effects of BCL6 on p53 and cell-cycle-inhibitory proteins-are also potentially interesting in DLBCL (43,44). One recent study demonstrated that treatment of DLBCL cell lines with pandeacetylone inhibitors in combination with niacinamide produced synergistic toxicity in GCB over ABC subtypes and led to acetylation of BCL6 and p53 (44). In a phase I proof-ofprinciple study, 24% of patients with relapsed lymphoma attained a response to vorinostat and niacinamide.…”
Section: Pre-rituximabmentioning
confidence: 99%
“…Drugs such as ibrutinib, proteasome inhibitors, and lenolidomide appear to be more active in the ABC phenotype, and are now being integrated into upfront R-CHOP-based chemotherapy regimens in randomized clinical studies. In contrast, other studies have optimized histone deacetylase inhibitors to target the Bcl-6-p53 axis in GC-derived DLBCL with promising results (17). In this particular example, we have become more knowledgeable, as data and information from efforts in quantitative experimentation are translated into clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…83 Rational targeting of actionable mutated genes in DLBCL is nevertheless a challenge, particularly after the discovery of an unexpected high grade of mutational/genetic heterogeneity found in the different NGS studies of human DLBCLs, 72 and following the observations that ongoing acquisition of mutations and intratumoral clonal heterogeneity are frequent findings in DLBCL. 13 Both the prognostic and predictive value of these mutations is still a matter of active research.…”
mentioning
confidence: 99%
“…66 Opportunities for targeting GC-DLBCL have also emerged from the study by Amengual and co-workers, which recently demonstrated that treatment of DLBCL cell lines with pan-DAC inhibitors in combination with niacinamide produces synergistic cytotoxicity in GC-DLBCL, correlated with acetylation of both Bcl6 and p53. 83 Rational targeting of actionable mutated genes in DLBCL is nevertheless a challenge, particularly after the discovery of an unexpected high grade of mutational/genetic heterogeneity found in the different NGS studies of human DLBCLs, 72 and following the observations that ongoing acquisition of mutations and intratumoral clonal heterogeneity are frequent findings in DLBCL. 13 Both the prognostic and predictive value of these mutations is still a matter of active research.…”
mentioning
confidence: 99%